Positioning without using GNSS - Pintér, Marco; Raichl, Petr (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This thesis is aimed at the development of the localization system without using GNSS. The first part describes technologies, which can be used for localization of robots in known environment.Then positioning system based on UWB technology is designed. Additionally, localization system based on DWM1000 is designed and tested.
Keywords: Positioning, UWB, Trilateration, DWM1000